-6v+2(v-7)=22

Simple and best practice solution for -6v+2(v-7)=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6v+2(v-7)=22 equation:


Simplifying
-6v + 2(v + -7) = 22

Reorder the terms:
-6v + 2(-7 + v) = 22
-6v + (-7 * 2 + v * 2) = 22
-6v + (-14 + 2v) = 22

Reorder the terms:
-14 + -6v + 2v = 22

Combine like terms: -6v + 2v = -4v
-14 + -4v = 22

Solving
-14 + -4v = 22

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -4v = 22 + 14

Combine like terms: -14 + 14 = 0
0 + -4v = 22 + 14
-4v = 22 + 14

Combine like terms: 22 + 14 = 36
-4v = 36

Divide each side by '-4'.
v = -9

Simplifying
v = -9

See similar equations:

| 2r^2+2=5r | | 20=2(x-4)+2x | | 1.5t-150=450 | | 5w+9=-31 | | 2r^4+46r^2-100=0 | | 2y+14x=0 | | 2(4X-9)=40 | | -3=6(v+2)-3v | | w+l-2.8l=4.3 | | f(3)=-2(3) | | 50h+100=x | | 4-x^2+16y^2=0 | | 2x^2-3=197 | | -3(2x-2)=45+3 | | 6x^3+21x^2-45x= | | 64=4xf | | 3x+19*5=2 | | 2(y-6)=12 | | (w)(w+2)=40 | | 10x^4-9x^3= | | b+23.19=38.72 | | 3y+4=x+14 | | e^3x=87 | | 5(3a+2)=12a+11 | | 25+x^2=225 | | (5w)*(5w+18)=-81 | | 0=x^3+64 | | -8+6n=-50 | | 7xv=28 | | -8n-1=15 | | x+3.6=-7.1 | | 4x-12.5=3.8 |

Equations solver categories